Shifu, Soul of Chinese Anarchism - Krebs, Edward S. (Rowman & Littlefield Publishers, 1998)
The most comprehensive study of Shifu available, this valuable work explores the life and political milieu of a central figure in Republican China. Born in 1884, Shifu was brought down in 1915 by overwork, poverty, and tuberculosis. Yet during that short span, he became the most influential anarchist of his time. Drawing on a wealth of primary source material, Krebs provides an intellectual biography of this committed revolutionary and analyzes the importance of Shifu's thought during the New Culture-May Fourth years as his followers fought for influence with the Marxists and later over the issue of alliance with the Nationalists. Placing Shifu's life within the dynamic intellectual and political currents of the time, the author describes Shifu's early work as an assassin within the anti-Qing movement. Examining the influence on Shifu of Confucianism and Buddhism, Krebs highlights reform Buddhism's close relationship with revolutionary activism. Most significantly, Shifu's unflagging work to propagate anarchism during the early years of the Republic and his interactions with other socialists reveal a hitherto unknown level of activity among socialist revolutionaries. This important book thus offers fresh insights not only into the anarchist movement itself, but into the broader history of Chinese socialism as well.